1964
DOI: 10.1111/j.1151-2916.1964.tb14632.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Growth of Large Sound Crystals of Zinc Oxide

Abstract: Large (10 to 20 g) macroscopically sound ZnO crystals suitable for preliminary transducer and other studies have been grown hydrothermally at rates of from 10 to 15 mils per day. The factors found to be important in achieving good growth were (1) base concentration of growth solution, (2) temperature difference between dissolving and growth regions, (3) presaturation of growth solution, (4) warm-up procedure, (5) addition of Li+ to the growth solution to suppress dendrite formation, (6) etching to remove seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(114 citation statements)
references
References 10 publications
4
110
0
Order By: Relevance
“…In consequence, Bragg reflections assigned to ZnSe are more intense than those of ZnO due to coagulation of small to larger size crystallites and increase of long-range order at lower temperatures of annealing in consistency with the results of ZnSe, ZnO, and doped ZnO crystallization from solutions [51][52][53].…”
Section: Kcn-etching Of Cu(inga)se 2 Surfacesupporting
confidence: 82%
“…In consequence, Bragg reflections assigned to ZnSe are more intense than those of ZnO due to coagulation of small to larger size crystallites and increase of long-range order at lower temperatures of annealing in consistency with the results of ZnSe, ZnO, and doped ZnO crystallization from solutions [51][52][53].…”
Section: Kcn-etching Of Cu(inga)se 2 Surfacesupporting
confidence: 82%
“…However, when a slight small-angle grain boundary formed in the incipient spontaneous nucleation, the oriented growth could continue in different orientations, promoting the growth of bidirectional adhesive crystals. [11,25] Secondly, the speed of pressure release, which determined the saturated-vapor pressure of the solvents and the amount of ZnO that the system could dissolve, is another key factor determining the ZnO morphology. Obviously, it could influence the crystal nucleation and growth processes.…”
Section: Growth Processmentioning
confidence: 99%
“…[28][29][30][31] Recently it was shown that lateral epitaxial overgrowth (LEO) of ZnO films on (111) spinel substrates could be accomplished in water at 90°C. [32] One hydrothermal method has been commonly used to synthesize ZnO for more than 50 years [33,34] to grow single crystals (generally > 5 cm) by the slow dissolution of ZnO powder held at a higher temperature relative to a ZnO "seed" crystal held at a lower temperature, all within a high temperature (generally > 300°C) autoclave. Generally, "mineralizers" such as KOH, NaOH, and NH 4 OH are used to increase the solubility of ZnO powder and thus to increase the growth rate of the single crystals.…”
Section: Introductionmentioning
confidence: 99%